2019
DOI: 10.1021/acsomega.9b01194
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Hexavalent Chromium to Trivalent Chromium with Zero Chemical Footprint: Borohydride Exchange Resin and a Polymer-Supported Base

Abstract: Aqueous hexavalent chromium, Cr(VI), is rapidly reduced to trivalent chromium, Cr(III), by exposure to (polystyrylmethyl)trimethylammonium borohydride and with Amberlite-supported mild bases in a heterogeneous environment. Post-reaction removal of the insoluble reagents leaves no remediation-based chemical footprint in the source water. Time dependence with stirred and static conditions is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…had been developed for heavy metal removal . Among them, the adsorption approach is among the most popular ones because of the high efficiency, low cost, and easy handling. , To date, numerous facile adsorbents had been developed for the removal of Cr­(VI) from water, such as carbonaceous materials, polyaniline-loaded materials, minerals, and ion exchange. However, unsustainability and low adsorption capacity remain a major challenge for these materials. With the increasing emphasis on sustainability, researchers are recently shifting toward using high performance environmental-friendly renewable biobased adsorbent materials for the removal of toxic Cr­(VI) from water.…”
Section: Introductionmentioning
confidence: 99%
“…had been developed for heavy metal removal . Among them, the adsorption approach is among the most popular ones because of the high efficiency, low cost, and easy handling. , To date, numerous facile adsorbents had been developed for the removal of Cr­(VI) from water, such as carbonaceous materials, polyaniline-loaded materials, minerals, and ion exchange. However, unsustainability and low adsorption capacity remain a major challenge for these materials. With the increasing emphasis on sustainability, researchers are recently shifting toward using high performance environmental-friendly renewable biobased adsorbent materials for the removal of toxic Cr­(VI) from water.…”
Section: Introductionmentioning
confidence: 99%
“…The positive △H 0 value, representing an endothermic reaction, supports the observation that by increasing the temperature of the adsorption process the K c values and initial rate also increase. The relatively small △S 0 value suggests the replacement of CO We have previously observed that the fluid dynamics of resin-based Cr (VI) removal agents, specifically Cr (VI) reduction to Cr (III), contributed to the efficiency of the remediation (Regan et al 2019). Specifically, heterogeneous solutions containing resins that were in motion (stirring) were more efficient than static conditions due to a faster diffusion rate of chromate into the porous cavities.…”
Section: Resultsmentioning
confidence: 99%
“…Natural conversion of Cr (VI) to Cr (III) in chrome mines area can be done by Live Spirulina platensis on Bio-sorption, adsorptions, ion exchange, or filtration methods. Cr (VI) is available as HCrO 4and chromate at pH > 6.5 but in Groundwater, it is a byproduct of many industrial processes Regan et al [18].…”
Section: Review Of Literaturementioning
confidence: 99%